Human plasma vitamin E kinetics demonstrate rapid recycling of plasma RRR-alpha-tocopherol. - Traber, M G (1994)
A kinetic model of vitamin E transport in humans is described using data from our studies with deuterium-labeled stereoisomers of alpha-tocopherol (RRR- and SRR-). In normal subjects, both alpha-tocopherols are present at similar concentrations in chylomicrons, but by 24 hr, RRR-alpha-tocopherol is at higher plasma concentrations because RRR-alpha-tocopherol is preferentially incorporated into very low density lipoproteins, which are then secreted into plasma. In three nondiscriminator patients with familial isolated vitamin E deficiency, the fractional disappearance rates (mean +/- SD) of deuterium-labeled RRR- and SRR-alpha-tocopherols in plasma were 1.4 +/- 0.6 and 1.3 +/- 0.3 pools per day, respectively (difference, 0.1 +/- 0.3). In these patients, plasma concentrations of both RRR- and SRR-alpha-tocopherols decreased similarly to SRR-alpha-tocopherol in controls. In six controls, fractional disappearance rates of deuterium-labeled RRR-alpha-tocopherol (0.4 +/- 0.1 pool per day) were significantly (P < 0.01) slower than for SRR- (1.2 +/- 0.6). The differences (0.8 +/- 0.6 pool per day) between these two rates in controls estimate the rate at which RRR-alpha-tocopherol, which had left the plasma, was returned to the plasma. Although plasma labeled RRR-alpha-tocopherol concentrations in controls appear to change slowly, these data show that both RRR- and SRR-alpha-tocopherols leave the plasma rapidly, but only RRR-alpha-tocopherol is returned to the plasma, likely in nascent very low density lipoproteins. This recycling of RRR-alpha-tocopherol accounts for nearly 1 pool of alpha-tocopherol per day.